The politics of power Freeport in Suharto's Indonesia - Leith, Denise (University of Hawaii Press, 2003)
This is an analysis of the mining company Freeport's presence in Indonesia. It looks closely at the changing nature of power relations between Freeport and Major General Suharto, the Indonesian military, the traditional landowners (the Amungme and Kamoro) and environmental and human rights groups.